2016
DOI: 10.1007/s40615-016-0246-8
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Calculation of Allostatic Load Score: 21 Examples from NHANES

Abstract: After decades of resistance there is now a genuine consensus that disease cannot be prevented or even successfully treated unless the role of stress is addressed alongside traditionally recognized factors such as genes and the environment. Measurement of allostatic load, which is quantified by the allostatic load score (ALS), is one of the most frequently used methods to assess the physiologic response to stress. Even though there is universal agreement that in the calculation of ALS, biomarkers from three cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
140
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(162 citation statements)
references
References 26 publications
(20 reference statements)
3
140
0
Order By: Relevance
“…For example, around 18 different ALoad calculations and 26 different biomarkers have been used in various studies using data from the National Health and Nutrition Examination Survey (NHANES). 7 However, research on ALoad index calculations in children is limited, and prior studies have utilized different combinations of bio-markers. 8,9 While there is no consensus on how to measure ALoad, the use of a previously published scoring system or developing a new definition tailored to a specific question is preferred.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, around 18 different ALoad calculations and 26 different biomarkers have been used in various studies using data from the National Health and Nutrition Examination Survey (NHANES). 7 However, research on ALoad index calculations in children is limited, and prior studies have utilized different combinations of bio-markers. 8,9 While there is no consensus on how to measure ALoad, the use of a previously published scoring system or developing a new definition tailored to a specific question is preferred.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 While there is no consensus on how to measure ALoad, the use of a previously published scoring system or developing a new definition tailored to a specific question is preferred. 7 Despite the variability in ALoad indexes, its use in predicting health risk associated with stress has been well documented, and it has been shown that the ALoad index improves the prediction of mortality and health outcomes compared with the use of metabolic syndrome components alone. 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the concept of measuring biologic stress by an allostatic load score (ALS) is decades old (1, 2), no consensus exists on which biomarkers to include in calculating ALS (12, 13). After reviewing the literature, we felt that studies of ALS, which focused on African-Americans and/or Hispanic immigrant populations, may have the most relevance to the African immigrant experience (12).…”
Section: Introductionmentioning
confidence: 99%
“…After reviewing the literature, we felt that studies of ALS, which focused on African-Americans and/or Hispanic immigrant populations, may have the most relevance to the African immigrant experience (12). Therefore, we chose the ALS formulation used by both Geronimus et al and Kaestner et al (4, 8).…”
Section: Introductionmentioning
confidence: 99%